Blocking TNF-α inhibits angiogenesis and growth of IFIT2-depleted metastatic oral squamous cell carcinoma cells. Issue 2 (28th January 2016) - Lai, Kuo-Chu; Liu, Chung-Ji; Lin, Tsung-Jen; Mar, Ai-Chung; Wang, Hsiu-Hua; Chen, Chi-Wei; Hong, Zi-Xuan; Lee, Te-Chang
Highlights: IFIT2-depleted OSCC cells exhibit enhanced metastatic activity and chemoresistance. TNF-α is upregulated in IFIT2-depleted metastatic OSCC cells. Blocking TNF-α abolishes the in vivo angiogenesis of IFIT2-depleted metastatic cells. Golimumab inhibits tumor growth and metastasis of IFIT2-depleted metastatic cells. Abstract: Our previous study demonstrated that the depletion of interferon-induced protein with tetratricopeptide repeats 2 (IFIT2) promoted metastasis and was associated with a poor prognosis in patients with oral squamous cell carcinoma (OSCC). Our current study explores the major downstream signaling involved in IFIT2 depletion-induced OSCC metastasis. To this end, we used two cell lines (designated sh-control-xeno and sh-IFIT2-xeno) derived from human OSCC xenografts expressing sh-control and sh-IFIT2, respectively, and one metastatic OSCC subline (sh-IFIT2-meta) from an IFIT2-depleted metastatic tumor. We found that the sh-IFIT2-meta cells proliferated more slowly than the sh-control-xeno cells but exhibited higher migration and chemoresistance. Using microarray technology and Ingenuity Pathway Analysis, we found that TNF-α was one of the major downstream targets in IFIT2-depleted OSCC cells. Quantitative real-time PCR, western blotting, and ELISA results confirmed that TNF-α was upregulated in the sh-IFIT2-meta cells. Blocking TNF-α abolished the angiogenic activity induced by the sh-IFIT2-meta cells. Furthermore, the human-specific TNF-α antibody golimumab significantly inhibited in vivo angiogenesis, tumor growth and metastasis of sh-IFIT2-meta cells. These results demonstrate that IFIT2 depletion results in TNF-α upregulation, leading to angiogenesis and metastasis of OSCC cells.